Fostering Effective Workforce Diversity Management in Nigerian Organizations: The Challenge of Human Resource Management - Akinnusi, David M.; Sonubi, Olubukunola O.; Oyewunmi, Adebukola E. (International Review of Management and Marketing, 2017)
The paper provides a conceptual understanding and significance of diversity and especially workplace diversity in Nigeria, drawing on previous studies. Naturally, the practice of HRM cannot be divorced from the socio-cultural, economic, political and legal environments of the nation. As the giant of Africa, with a population of about 180 million, about half of whom are of working age, Nigeria is an attractive market for multinationals from across the globe, and simultaneously fast becoming a melting pot of cultures and a nation where businesses should be booming but for the gross mismanagement, corruption and inept leadership. One of Nigeria’s most critical challenges, therefore, is the effective management of its workforce diversity, a litmus test for the maturity of HRM. The role and the capacity of human resource management function (HRM) in managing workplace diversity in Nigeria is critically assessed and based on an integrated conceptual framework, the challenges of managing workplace diversity in Nigeria is discussed and future research directions are indicated. Keywords: Human resource management, workforce diversity, Nigeria, diversity management JEL Classification: M12